E Fora Do Story, Você Está Bem? As Consequências Do Uso Do Instagram Para A Saúde Mental - Lima, Mateus Soares dos Santos (Universidade Federal do Tocantins, 2022)
This work addresses the consequences that the exacerbated use of Instagram, as well as other social networks, can cause to the mental health of its users. In the format of a multiplatform content, materials were developed to meet different internet segments, such as web reportage, informative teaser and Web Story for social networks. Thus, all the material was developed based on data collected through a survey developed with 120 Instagram users. With media elements that add value, such as infographics and carousel images, the multimedia reportage is a journalistic narrative about the reality experienced in the virtual environment of Instagram. In the construction of this narrative, testimonials of users who have suffered some of the situations mentioned throughout the report were collected, being also elucidated by the testimony of a psychologist who works in the area of behavioral study.